2011
DOI: 10.1586/era.11.188
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma of cystectomy in old-old and oldest-old patients

Abstract: Bladder cancer (BC) is a disease of the elderly, with a peak incidence at 85 years. If life expectancy continues to increase in such a way that it is, in 20 years nearly half of the population will be considered elderly. The incidence of BC will also dramatically increase in proportion to this and, subsequently, a cure is needed. Currently, only 4-11% of elderly individuals with muscle-invasive BC undergo radical extirpative surgery; a number that is evidently too low when we consider that the cancer-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…In the coming decades, demographic changes in Western countries will result in a further aging population [20]. The incidence of BC also increases with age and is 11-fold higher in patients ≥65 years compared to patients <65 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the coming decades, demographic changes in Western countries will result in a further aging population [20]. The incidence of BC also increases with age and is 11-fold higher in patients ≥65 years compared to patients <65 years.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of BC also increases with age and is 11-fold higher in patients ≥65 years compared to patients <65 years. In addition, elderly patients (≥65 years) have a 16-fold higher BC mortality rate compared to patients <65 years, and this increases with advanced age [20,21,22]. Age also represents a strong and independent risk factor for the presence of BC, as the peak age for BC is advancing and now estimated at 85 years [20,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, RC demonstrates a 3-5-fold higher perioperative mortality in septuagenarians (5.4%) and octogenarians (9.2%) in comparison to patients ≤ 69 years (2%) (5). Some studies, however, have demonstrated that selected older patients have similar peri-operative outcomes as younger patients (6)(7)(8). Bladder sparing treatment in a selected group of octogenarians has also been successfully demonstrated by Wehrberger et al (9).…”
Section: Introductionmentioning
confidence: 92%
“…Currently, only 4-11% of individuals at advanced ages that present muscle-invasive cancer undergo radical dissecting surgery, with a rate of complications of 24-60%, and a 90-day mortality rate of 10% [15].…”
Section: Discussionmentioning
confidence: 99%